SOSIALISASI KEWIRAUSAHAAN DALAM UPAYA PENINGKATAN UMKM DI NAGARI MUARA INDERAPURA UNTUK MENINGKATKAN PEREKONOMIAN - Putra, Eka; Bustami, Yuserizal; Mahabbati, Suci; Azhar, Azhar; Afrilia, Annisa (Institut Agama Islam Negeri Kerinci, 2024)
Along with the times, the world of technology is growing, so MSMEs in an economic society must keep up with technological developments to maintain their existence in business and business management, as micro, small, and medium enterprises (MSMEs) play a key role in growth. Indonesian economy. MSMEs account for 85% of the employment rate. In a business, it is necessary to study the business's survival. However, in reality, the community only focuses on the status of working as an employee in a company to earn income. Therefore, cultivating a community with a socialization approach imbued with entrepreneurship is done to help motivate people to run independent businesses. Empowerment refers to the ability of individuals, especially disadvantaged groups, to find productive resources that help them increase their income and participate in development and decision-making processes. The results of this study indicate that the people of Muara Inderapura Village have great potential for village economic development through MSME. Factors supporting community development in the economic field include abundant natural and human resources and strong community participation. While the inhibiting factors are capital, facilities.